Low-dose studies of bystander cell killing with targeted soft X rays. - Schettino, G; Folkard, M; Prise, K; Vojnovic, B; Held, K; Michael, B (2003)
The Gray Cancer Institute ultrasoft X-ray microprobe was used to quantify the bystander response of individual V79 cells exposed to a focused carbon K-shell (278 eV) X-ray beam. The ultrasoft X-ray microprobe is designed to precisely assess the biological response of individual cells irradiated in vitro with a very fine beam of low-energy photons. Characteristic CK X rays are generated by a focused beam of 10 keV electrons striking a graphite target. Circular diffraction gratings (i.e. zone plates) are then employed to focus the X-ray beam into a spot with a radius of 0.25 microm at the sample position. Using this microbeam technology, the correlation between the irradiated cells and their nonirradiated neighbors can be examined critically. The survival response of V79 cells irradiated with a CK X-ray beam was measured in the 0-2-Gy dose range. The response when all cells were irradiated was compared to that obtained when only a single cell was exposed. The cell survival data exhibit a linear-quadratic response when all cells were targeted (with evidence for hypersensitivity at low doses). When only a single cell was targeted within the population, 10% cell killing was measured. In contrast to the binary bystander behavior reported by many other investigations, the effect detected was initially dependent on dose (<200 mGy) and then reached a plateau (>200 mGy). In the low-dose region (<200 mGy), the response after irradiation of a single cell was not significantly different from that when all cells were exposed to radiation. Damaged cells were distributed uniformly over the area of the dish scanned (approximately 25 mm2). However, critical analysis of the distance of the damaged, unirradiated cells from other damaged cells revealed the presence of clusters of damaged cells produced under bystander conditions.